Metabolic syndrome is common and persistent in youth‐onset type 2 diabetes: Results from the TODAY clinical trial. (5th June 2015) - Weinstock, Ruth S.; Drews, Kimberly L.; Caprio, Sonia; Leibel, Natasha I.; McKay, Siripoom Vudhipoom; Zeitler, Philip S.; for the TODAY Study Group
<x xml:space="preserve">Abstract</x> Objective To examine the prevalence of metabolic syndrome (MetS) in youth‐onset type 2 diabetes in the Treatment Options for Type 2 Diabetes in Adolescents and Youth (TODAY) study. Methods Prevalence of MetS (ATP III definition) was compared at baseline (n = 679) and at 6 (n = 625) and 24 months (n = 545) using chi‐square tests. Laboratory data were examined between MetS classifications at each time point using ANOVA. Results Baseline prevalence of MetS was 75.8% and did not differ by treatment group or change over time. MetS was more common in females (83.1%) than males (62.3%; P < 0.0001) at baseline; this difference persisted over 24 months. Prevalence of MetS was similar between ethnic groups at baseline but greater in Hispanics (82.7%) vs. non‐Hispanic Whites (67.5%; P = 0.0017) and non‐Hispanic Blacks (72.7%; P = 0.0164) at 24 months. Although MetS was common in participants with hemoglobin A1c < 7.0% (74.4% at baseline; no significant change over 24 months), it was more common in those who did not maintain glycemic control at 6 months (80.3%; P = 0.0081). Elevated C‐reactive protein, ALT, IL‐6, and PAI‐1 levels were more frequent with MetS. Conclusions Persistent high prevalence of MetS in youth‐onset diabetes, even with excellent glycemic control, is of concern given the associated increased cardiovascular risk.